Effects of rumen protected fat on growth performance and digestibilities in sheep - Ee, Li Yen (2017)
The effects of different types of rumen protected fat (RPF) supplementation on growth performance and digestibility of sheep were studied. This study was carried out due to limited information on digestibility and feeding of different types of RPF in sheep. Forty-five male sheeps of 24.81 ± 5.29 kg were used in complete randomized design (nine sheeps per treatment). Five isonitrogenous and isocaloric dietary treatments were Treatment 1 (T1, palm oil), Treatment 2 (T2, RPF with calcium), Treatment 3 (T3, RPF without calcium), Treatment 4 (T4, RPF without lecithin) and Treatment 5 (T5, RPF with lecithin). The feeding trial was conducted for four weeks; however, digestibility trial was conducted for a week on 15 sheeps (three sheeps per treatment). The sheep were weighed at weeks 0, 2 and 4. Blood samples were collected before and after the study for determination of fatty acid (FA) profile in blood serum. Fecal samples were collected during digestibility trial and used to calculate apparent nutrient digestibility. Thirty-five sheeps were slaughtered for meat quality analysis. Average daily gain, feed conversion ratio and dry matter intake were not affected (P>0.05) by the treatments. Apparent nutrient digestibility values in T5 were significantly higher (P<0.05) for ether extract, crude protein and crude fiber compared to other treatments. Neither the inclusion of RPF with calcium or lecithin impacted (P>0.05) carcass characteristics but only drip loss after 24 h showed significant differences with the lowest value (1.51%) observed in T4. Aging after 7 d resulted in brighter meats, less redness and generally increased yellowness. Polyunsaturated FA in blood serum showed significant increase for all treatments and T4 yielded the most significant reduction (4.22%) for n-6/n-3 FA ratio. There are no negative effects of RPF on the measured parameters as compared with palm oil.